Probability Method for Analyzing the Prevalence of Calcium, Iron, Zinc, and Vitamin D Deficiencies among Indonesian Adolescents - Anwar, Khoirul; Hardinsyah, Hardinsyah; Damayanthi, Evy; Sukandar, Dadang (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2018)
The objective of this study was to analyse the prevalence of Ca, Fe, Zn, and vitamin D deficiency (micronutrient deficiency-MD) in adolescents using probability method (PBM) and cut-off point method (CPM). This study utilized secondary data from nation-wide Basic Health survey (Riskesdas) 2010 from the Ministry of Health, in which data on nutrient intakes were collected using 24-hour recall. The total subjects were 24,833 Indonesian males and females aged 13-18 years. The nutrient requirement of each micronutrient was derived from the Institute of Medicine (IOM). The prevalence of MD using PBM was analysed by calculating the proportion of subjects with intake of below their requirement in the population. The prevalence of MD using CPM analysed by applying three cut-off point i.e. less than 100% (CP-100), less than 85% (CP-85), and less than 70% (CP-70) of the micronutrient requirement. Results showed that the prevalence of MD was high both calculated by PBM and CPM. In both methods, the prevalence of MD deficiencies were slightly higher in females than in males, and in older age group than younger age group. The prevalence of MD calculated using PBM was higher compared to the CPM-85 and CPM-70, but not always higher compared to CPM-100. Overall, the nutrient density of Ca, Fe, Zn and vitamin D for both male and female adolescents were below recommendations, however the nutrient density of Ca, Zn, and vitamin D in females were higher than in males (p<0,05). This study concludes that the intakes of micronutrient (Ca, Fe, Zn, and , D) among Indonesian adolescent were far below the requirement based on PBM and CPM calculations. In addition, the nutrient density of each micronutrient was classified as inadequate. This implies the importance of improvement in the quantity and quality of micronutrient intakes among Indonesian adolescents through increasing the consumption of fish, meat, eggs, legumes, milk, and green vegetables.